(untitled) (Taylor & Francis, 2005)
The degradable nature of high-performance, wood-based materials is an attractive advantage when considering environmental factors such as sustainability, recycling, and energy/resource conservation. The Handbook of Wood Chemistry and Wood Composites provides an excellent guide to the latest concepts and technologies in wood chemistry and bio-based composites. The book analyzes the chemical composition and physical properties of wood cellulose and its response to natural processes of degradation. It describes safe and effective chemical modifications to strengthen wood against biological, chemical, and mechanical degradation without using toxic, leachable, or corrosive chemicals. Expert researchers provide insightful analyses of the types of chemical modifications applied to polymer cell walls in wood, emphasizing the mechanisms of reaction involved and resulting changes in performance properties. These include modifications that increase water repellency, fire retardancy, and resistance to ultraviolet light, heat, moisture, mold, and other biological organisms. The text also explores modifications that increase mechanical strength, such as lumen fill, monomer polymer penetration, and plasticization. The Handbook of Wood Chemistry and Wood Composites concludes with the latest applications, such as adhesives, geotextiles, and sorbents, and future trends in the use of wood-based composites in terms of sustainable agriculture, biodegradability and recycling, and economics. Incorporating over 30 years of teaching experience, the esteemed editor of this handbook is well-attuned to educational demands as well as industry standards and research trends.
Keywords: Wood,Engineered wood; Chemistry,Handbooks, manuals, etc.,Handbooks, manuals, etc